EFFECTS OF THE SEAT CUSHION OSCILLATORY PARAMETERS ON VIBRATION EXPOSURE AND DYNAMIC SEAT COMFORT IN THE BUS - Sekulić, Dragan; Ivković, Ivan; Mladenović, Dušan (Journal of Applied Engineering Science, 2017)
The paper analyzed the influence of the passenger seat’s cushion oscillatory parameters (stiffness/damping) on ride comfort and dynamic seat comfort. The analysis was done using a linear in-line oscillatory seat-human model with 4 degrees of freedom (DOF) defined in Matlab/Simulink. For the oscillatory excitations of the in-line model, the vertical accelerations of the bus floor under the users’ seats were used. Bus floor accelerations were obtained by simulation using validated spatial oscillatory intercity bus model with 65 DOF defined in the ADAMS/View software. The ride comfort was assessed by the criteria of ISO 2631/1997 standard. The seat effective amplitude transmissibility (SEATrms) parameter was considered for analyzing the dynamic seat comfort. It was found that passengers in the rear part of the bus had a lower level of ride comfort than the passengers in the front part of the bus. The intensities of the bus floor vertical accelerations for the rear part were mainly concentrated in the frequency range of 5-10 Hz. Passengers at the rear had lower SEATrms values than those at the front. The SEATrms values increased noticeably with the increase in the cushion stiffness, but those values were below 100% for all considered users. Increase in the cushion damping slightly decreased SEATrms values.
Keywords: ride comfort; dynamic seat comfort; oscillatory models; standard ISO 2631; Matlab/Simulink; ADAMS/View